Generation of a Collection of Mutant Tomato Lines Using Pooled CRISPR Libraries. Issue 4 (23rd June 2017) - Jacobs, Thomas B.; Zhang, Ning; Patel, Dhruv; Martin, Gregory B.
Abstract : Plant transformation with pooled CRISPR libraries enables the rapid production of mutant lines for functional screens. Abstract: The high efficiency of clustered regularly interspaced short palindromic repeats (CRISPR )-mediated mutagenesis in plants enables the development of high-throughput mutagenesis strategies. By transforming pooled CRISPR libraries into tomato ( Solanum lycopersicum ), collections of mutant lines were generated with minimal transformation attempts and in a relatively short period of time. Identification of the targeted gene(s) was easily determined by sequencing the incorporated guide RNA(s) in the primary transgenic events. From a single transformation with a CRISPR library targeting the immunity-associated leucine-rich repeat subfamily XII genes, heritable mutations were recovered in 15 of the 54 genes targeted. To increase throughput, a second CRISPR library was made containing three guide RNAs per construct to target 18 putative transporter genes. This resulted in stable mutations in 15 of the 18 targeted genes, with some primary transgenic plants having as many as five mutated genes. Furthermore, the redundancy in this collection of plants allowed for the association of aberrant T0 phenotypes with the underlying targeted genes. Plants with mutations in a homolog of an Arabidopsis ( Arabidopsis thaliana ) boron efflux transporter displayed boron deficiency phenotypes. The strategy described here provides a technically simple yet high-throughput approach for generating a collection of lines with targeted mutations and should be applicable to any plant transformation system.